Analysis of Reading Comprehension Questions by Using Revised Bloom’s Taxonomy on Higher Order Thinking Skill (HOTS) - Febrina Febrina; Bustami Usman; Asnawi Muslem (Universitas Syiah Kuala, 2019)
The objective of this research was to investigate the three up levels of cognitive domain of revised Bloom’s Taxonomy used in the textbook entitled Bahasa Inggris SMA/MA/SMK/MAK grade 11 th semester 1, namely analyzing level (C4), evaluating level (C5), and creating level (C6). Using the descriptive qualitative method and content analysis, this study examined the questions in the reading comprehension tasks only to determine to what extent the reading comprehension questions emphasize on Higher Order Thinking. This research focused on analyzing the Bahasa Inggris SMA/MA/SMK/MAK textbook grade 11 th semester 1 published by the Ministry of Education and Culture. The researcher collected and listed the questions in the reading comprehension tasks and then calculated the percentage and frequencies of each level of cognition in each separate book chapter and in all five combined book chapters. The results showed that the most dominant level in the textbook was higher order thinking skills HOTS). It was 66.8 % of 100 % while it was 33.4 % for lower order thinking skills LOTS). It indicated that this textbook concentrated more on higher –level thinking questions than lower lever thinking.